Oil initial in Place (OIIP) Determination Using the Volumetric Method of the Wells F1, F2, NC74- in Sirt Basin - Salem Kalefah Fattouh; Najw Abdulmajid Salim Bahroun; Abdulqadir Emran ALmukhtar (Surman Journal of Science and Technology, 2026)
Oil and gas industry is full with many challenges for a wide range of operating jobs, one of these challenges throughout the early life of the oil and/or gas field is to determine the petrophysical properties of the production zone and predict of many million barrels of hydrocarbons are there. The aim of this study is to determine the original oil in place (OOIP) using well logging methods to determine the petrophysical properties of the potential production zone for two wells in Beda oil field. Through calculating the petrophysical properties of wells F1 and F1 (NC74)-F2, it was found that the average porosity was 27.76%, while the clay content was low and did not affect the porosity or permeability, ranging between 10 and 20%. The oil saturation rate was 77.60%, which is a good and economical rate. The oil reserves of the two wells (oil reservoir) present in the reservoir amount to 285MM STB.